2021
DOI: 10.3390/genes12111675
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Acquisition of p53 Functions

Abstract: Remarkably, the p53 transcription factor, referred to as “the guardian of the genome”, is not essential for mammalian development. Moreover, efforts to identify p53dependent developmental events have produced contradictory conclusions. Given the importance of pluripotent stem cells as models of mammalian development, and their applications in regenerative medicine and disease, resolving these conflicts is essential. Here we attempt to reconcile disparate data into justifiable conclusions predicated on reports … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 175 publications
0
6
0
Order By: Relevance
“…1j, Supplementary Tables 7, 8). The prediction of p53 activation is also supported by differential expression of several p53 target genes (Jaiswal et al ., 2021), such as MDM2 and PPM1D (feedback); CDKN1A, BTG2, GADD45A (cell-cycle arrest); TNFRSF10B (apoptosis), DDB2 and RRM2B (DNA- repair); FDXR (metabolism) and SESN1 (translation control) (Supplementary Table 2). Other pathways of interest related to DNA damage and p53, such as cellular response to DNA damage stimulus and DNA damage response signal transduction by p53 class mediator were specific to the aneuploid group.…”
Section: Resultsmentioning
confidence: 83%
“…1j, Supplementary Tables 7, 8). The prediction of p53 activation is also supported by differential expression of several p53 target genes (Jaiswal et al ., 2021), such as MDM2 and PPM1D (feedback); CDKN1A, BTG2, GADD45A (cell-cycle arrest); TNFRSF10B (apoptosis), DDB2 and RRM2B (DNA- repair); FDXR (metabolism) and SESN1 (translation control) (Supplementary Table 2). Other pathways of interest related to DNA damage and p53, such as cellular response to DNA damage stimulus and DNA damage response signal transduction by p53 class mediator were specific to the aneuploid group.…”
Section: Resultsmentioning
confidence: 83%
“…It is noteworthy that p53 exhibits widespread expression in various regions of the brain and the entire eye of adult mice. The expression is particularly high in the retina and optic nerve, while also accounting for a substantial portion, up to 70%, p53 is expressed at high levels during normal embryogenesis and development, regulating cell cycle and apoptosis [90], in the central nervous system (CNS) as well as other anatomical compartments such as olfactory bulb and eye [91][92][93][94][95][96]. Studies in an animal model showed a marked role of p53 during early embryonic ocular development, highlighting ocular abnormalities of hyaloid vasculature, vitreal opacities, retinal folding, and nerve fiber hypoplasia in mice defective for p53, according to their genetic background [97].…”
Section: The Role Of P53 In Tissue and Ocular Homeostasismentioning
confidence: 99%
“…Consequently, in cases of severe or excessive DNA damage, p53 induces apoptosis or senescence. Furthermore, activation of p53 suppresses pluripotency genes, such as Nanog, allowing differentiation to proceed [67,68].…”
Section: Patient Selection (Whom?)mentioning
confidence: 99%